Pulmonary hyperpolarized (129) Xe morphometry for mapping xenon gas concentrations and alveolar oxygen partial pressure: Proof-of-concept demonstration in healthy and COPD subjects - Ouriadov, A; Farag, A; Kirby, M; McCormack, D G; Parraga, G; Santyr, G E (Magnetic resonance in medicine, 2015)
Diffusion-weighted (DW) hyperpolarized (129) Xe morphometry magnetic resonance imaging (MRI) can be used to map regional differences in lung tissue micro-structure. We aimed to generate absolute xenon concentration ([Xe]) and alveolar oxygen partial pressure (pA O2 ) maps by extracting the unrestricted diffusion coefficient (D0 ) of xenon as a morphometric parameter. In this proof-of-concept demonstration, morphometry was performed using multi b-value (0, 12, 20, 30 s/cm(2) ) DW hyperpolarized (129) Xe images obtained in four never-smokers and four COPD ex-smokers. Morphometric parameters and D0 maps were computed and the latter used to generate [Xe] and pA O2 maps. Xenon concentration phantoms estimating a range of values mimicking those observed in vivo were also investigated. Xenon D0 was significantly increased (P = 0.035) in COPD (0.14 ± 0.03 cm(2) /s) compared with never-smokers (0.12 ± 0.02 cm(2) /s). COPD ex-smokers also had significantly decreased [Xe] (COPD = 8 ± 7% versus never-smokers = 13 ± 8%, P = 0.012) and increased pA O2 (COPD = 18 ± 3% versus never-smokers = 15 ± 3%, P = 0.009) compared with never-smokers. Phantom measurements showed the expected dependence of D0 on [Xe] over the range of concentrations anticipated in vivo. DW hyperpolarized (129) Xe MRI morphometry can be used to simultaneously map [Xe] and pA O2 in addition to providing micro-structural biomarkers of emphysematous destruction in COPD. Phantom measurements of D0 ([Xe]) supported the hypotheses that differences in subjects may reflect differences in functional residual capacity.